Study of the wettability and the corrosion protection of the hybrid silane (3-aminopropyl) triethoxysilane (APTES) and (3-glycidyloxypropyl) trimethoxysilane (GPTMS) film on galvannealed steel - Souza,Kleber Gustavo da Silva (2020)
ABSTRACT In this work, the wettability of the galvannealed surface pretreated with the hybrid silane APTES/GPTMS film was measured by sessile drop method. The coatings were applied on the substrate from dip-coating method and dried in an oven. The study followed an experimental factorial design, 3³, with contact angle as response. The corrosion resistance was evaluated by electrochemical techniques and the surface morphology was characterized by scanning electron microscopy. The wettability results showed the best condition for galvannealed steel pretreated with the hybrid silane film for 2:1 APTES:GPTMS ratio, 2% silane concentration and 150 min of hydrolysis time, because the result may be related to a higher rate of hydrolysis of the silanes that is influenced by both the functional group present and by the type and number of hydrolyzed groups, resulting consequently in a higher availability of silanol groups in solution, promoting a greater crosslinking of the film on the metallic substrate.